A UML 2.0 profile web design framework for modeling complex web application - Mubin, Siti Azreena; Jantan, Azrul Hazri (IEEE (IEEE Xplore), 2014)
Web applications have been developed from a simple static information webpage to a more complex web application, supporting complex processes and transactional workflows. The existing of numerous modeling concepts and design features in web applications, thus raises new issues on modeling approach. In this paper, we present and discuss the uses of user interaction diagram, object-oriented approach and Unified Modeling Language (UML) notation for complex web applications. Our main objective is to propose a web application design model which is based on UML 2.0 profile and stereotypes. We propose user interaction diagram to capture users' information from use case diagram and specific UML modeling elements to model conceptual, navigational and user interface features of complex web applications. The uniqueness of our proposed design model stands in the design patterns modeling approaches. At the end of the paper, some future enhancements of the design model will be explained and briefly summarized.